Comparison of turbinoplasty surgery efficacy in patients with and without allergic rhinitis - Hamerschmidt,Rodrigo (2016)
ABSTRACT INTRODUCTION: Turbinoplasty is a procedure that aims to reduce the size of the inferior turbinate through exuberant bone removal with high mucosal preservation. The procedure is recommended for patients with or without allergic rhinitis and those showing irreversible hypertrophy of inferior turbinates. OBJECTIVE: To evaluate the efficacy of inferior turbinoplasty for obstructive and non-obstructive symptoms in patients with or without allergic rhinitis. METHODS: Prospective study with 57 patients who underwent inferior turbinoplasty. They were evaluated for nasal obstruction, snoring, facial pressure, smell alterations, sneezing, nasal itching and runny nose symptoms, surgery time, and intraoperative bleeding. The last evaluation took place three months after surgery. RESULTS: Thirty-nine patients with allergic rhinitis and 18 without were assessed. Ninety days after surgery, 94.7% of patients showed degrees IV and V of breathing improvement; 89.5% showed moderate or complete improvement in snoring; all patients showed smell improvement (only one showed moderate improvement; all the others had full improvement); 95.5% experienced complete facial pressure improvement; and 89.7% showed moderate to complete improvement in nasal itching and runny nose symptoms, as well as in sneezing. CONCLUSION: The efficacy of inferior turbinoplasty was confirmed not only for obstructive symptoms, but also for non-obstructive symptoms in patients with and without allergic rhinitis.